Pathways to support: a qualitative investigation of community health workers'role in coordinating disability services in India - Lorane Scaria; Rachel Blance-Palmer; Lynette Joubert; Saju Madavanakadu Devassy (Discover Social Science and Health)
Abstract Aim To explore the roles and responsibilities of Accredited Social Health Activists (ASHAs) and Anganwadi Workers (AWWs) in providing support to people living with disability and their households. Subject and methods The current qualitative study involves a sequential research design involving two phases of qualitative data collection. Phase one includes a brief qualitative interview with thirty-three ASHAs to map the key themes of their work in the disability sector and how they work alongside AWWs. Phase two includes in-depth interviews with seven AWWs to explore their perspectives on the services available to people with disabilities in India, including the practical, emotional, and social support they provide and how they work alongside ASHAs. Thematic analysis was undertaken to analyze the results. Results The key responsibilities of the ASHAs were monitoring and connection, and facilitating support for practical tasks. Service mapping of AWWs identified four domains – identification and referral, service coordination, monitoring and psychosocial support. Collaborative tasks between the two cadres were identified as; health education, coordinated activities with healthcare centres, house visits, and implementation of public health programs. Conclusion The current study provides insights into community-based disability care in India, bringing a culturally relevant perspective to global conversations about disability support services. Community health workers are an excellent resource for multidimensional care for families of people with disabilities in India. Through effectively coordinated task-shifting and task-sharing strategies, ASHAs and AWWs can work alongside each other to implement interventions to improve the lives of people with disabilities and their households in India.